Favorable Outcomes in Older Recipients Receiving Simultaneous Pancreas Kidney Transplantation - Pooja Budhiraja, MD; Raymond L. Heilman, MD; Kunam S. Reddy, MBBS; Caroline C. Jadlowiec, MD; Hassan A. Khamash, MD; Jacob Ninan, MD; Swetha Reddy, MD; Hay Me Me, MD; Suman Misra, MD; Nitin Katariya, MD; Harini A. Chakkera, MD (Transplantation Direct, 2022)
Background. The objective of this study was to compare the long-term outcomes of older (50–65 y) type 1 diabetics with body mass index <35 kg/m2 and type 2 diabetics with body mass index <30 kg/m2 who received simultaneous pancreas kidney transplantation (SPKT) versus living donor kidney transplants (LDKTs). All subjects had insulin-dependent diabetes. Methods. This is a retrospective single-center study from July 2003 to March 2021 with a median follow-up of 7.5 y. Results. There were 104 recipients in the SPKT and 80 in the LDKT group. The mean age was 56 y in SPKT and 58 y in LDKT. There were 55% male recipients in the SPKT group versus 75% in LDKT. The duration of diabetes was 32 y in SPKT versus 25 y in LDKT. The number of preemptive transplants and length of dialysis were similar. However, the wait time was shorter for LDKT (269 versus 460 d). Forty-nine percent of the LDKT recipients received the organ within 6 mo of being waitlisted compared with 28% of SPKT recipients (P = 0.001). Donor age was lower in the SPKT group (27 versus 41 y). The estimated 5-y death censored kidney survival was 92% versus 98%, and 5-y patient survival was 86% versus 89% for SPKT versus LDKT. Death censored kidney and patient survival, acute kidney rejection by 1 y, and BK viremia were similar between the 2 groups. There were 17 pancreas graft losses within 1 y of transplant, the majority related to surgical complications, and it was not associated with increased mortality. Conclusions. SPKT in selected recipients aged 50 and above can have excellent outcomes similar to LDKT recipients.